2005
DOI: 10.1242/dev.01601
|View full text |Cite
|
Sign up to set email alerts
|

Lunatic fringe null female mice are infertile due to defects in meiotic maturation

Abstract: We have demonstrated that Notch genes are expressed in developing mammalian ovarian follicles. Lunatic fringe is an important regulator of Notch signaling. In this study, data are presented that demonstrate that radical fringe and lunatic fringe are expressed in the granulosa cells of developing follicles. Lunatic fringe null female mice were found to be infertile. Histological analysis of the lunatic fringe-deficient ovary demonstrated aberrant folliculogenesis. Furthermore, oocytes from these mutants did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 98 publications
(97 reference statements)
3
85
0
1
Order By: Relevance
“…One is the abnormal gap junction between the follicular granulosa cells and oocytes that might influence the development of oocytes and block the meiosis (Carabatsos et al 2000, Eppig 2001, Klinger & de Felici 2002, Hahn et al 2005. Several studies have demonstrated that the gap junctions during the development of follicles were required for the progression of the follicular development, and the intercellular connections were thought to be important for transporting small molecules facilitating the growth of mouse oocyte (Carabatsos et al 2000, Eppig 2001, Epifano & Dean 2002, Matzuk et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…One is the abnormal gap junction between the follicular granulosa cells and oocytes that might influence the development of oocytes and block the meiosis (Carabatsos et al 2000, Eppig 2001, Klinger & de Felici 2002, Hahn et al 2005. Several studies have demonstrated that the gap junctions during the development of follicles were required for the progression of the follicular development, and the intercellular connections were thought to be important for transporting small molecules facilitating the growth of mouse oocyte (Carabatsos et al 2000, Eppig 2001, Epifano & Dean 2002, Matzuk et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that Notch signaling is important for the regulation of primordial follicle formation. The first suggestion that Notch signaling might be involved in follicle formation came from analysis of lunatic fringe (Lfng) mutants (Hahn et al 2005). LFNG is part of the Fringe family of proteins that regulate Notch signaling (Bruckner et al 2000, Hicks et al 2000.…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 99%
“…Mutations of Fringe give Notch signaling defects that manifest at developmental boundaries in the formation of wings, legs and eyes in Drosophila [7]. In mammals, including humans [48], Lfng is required for Notch signaling during somitogenesis, and affects female meiosis [49] and T cell development in mice [47]. In vivo functions of Rfng are not noticeably developmental [10] and Mfng mutant mice have not been described.…”
Section: Abbreviationsmentioning
confidence: 99%